(untitled) (Journal of Economic Research & Business Administration, 2016)
Effective introduction of internal audit plays an important role of financial and economic situation of the bank. To date, the audit service is a developed view of areas of the economy. Terms administration audit in banking transactions confirmed as follows: the system of internal control, audit, oversight of the bank, organization audit. This article describes the control of banking operations in the implementation of the methodology of the internal audit of cash transactions and check the main sources of cash transactions. It also provides functions of internal control in the organization of banking audit, test conditions, and international standards, laws and banking regulations.